วาทกรรมเพลงเพื่อชีวิตในบริบทการเมืองไทย (พ.ศ. 2525-2550) - ณัฏฐณิชา นันตา (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
"Song for life" means song that presents the idea of "for better life and better social." The objectives of this research are to analyze the discourse of songs for life and to analyze the transferred idea and ideology of their contents between 1982 and 2007. The study selected 4 national song for life’s bands: Caravan, Carabao Pongthep Kradonchamnan and Phongsit Khompee and 3 regional song for life’s bands, Jaran Manopeth from the North, Saletae from the Northeast and Hammer from the South. Moreover, 4 periods in Thai political context were separated in this research; Semi Democracy (1982 - 1987), Democracy and Bubble Economy (1988-1996), Democracy and Crisis Economy (1997-2000), Democracy and Populism (2001-2007). For analysis result, main discourse and ideology of songs for life is pretension of entirely democracy including equality and justice. The term "Democracy", for which lyricists consist, has created for related 2 issues; Democracy as regime and Democracy as way of life. In order that, the details of discourse are difference depending on social economic and political dynamics. In addition, This research found that National song for life’s bands and regional song for life’s bands are different. National song for life’s bands reflected on construct social problem. For regional song for life’s bands presented by their local problem. The objective of song for life remains to "for better life and better social" meaning which is similar to previous definition. Due to social economic and political dynamics, the difference is that current song for life presents more variety and complexity as music movement. In addition the border between public and commercial media becomes decrease. The main reason is the commerce especially changing song for life’s production by constructed new meaning of song for life from the singer image. Thus song for life content has been changed by reducing original meaning. Originally, the content of song for life was created for Music for Movement. However, it has now become too flexible depending upon consumer’s demand. In this context, song for life has been criticized by many people.